The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1177/07356331211053383
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mind Mapping on Creative Thinking of Children in Scratch Visual Programming Education

Abstract: Scratch, a kind of visual programming software, has been widely used in instruction for primary school children. Scratch constructs a digital world for children to design, develop, and create coursework in which their creative thinking is fostered. Different instructional methods have been designed and implemented to stimulate children’s creative thinking skills through their coursework. This study investigated whether scaffolding construction with mind mapping promoted children’s creative thinking in a Scratc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 68 publications
0
15
0
2
Order By: Relevance
“…However, unlike the first objective that we discussed, the data confirm that the pandemic, together with the preventive measures in Spanish schools, had an impact on the experimental group that developed active methodologies, as supported by the study by Ref [ 68 ], especially in PEER_INT, POST_COM and TRANS_THINK in a negative way, although above the average evaluation. That is, working in the classroom as a group or exchanging ideas among peers through fields of computational thinking, such as robotics, programing or artificial intelligence, as supported by studies by Refs [ 41 , 42 , 43 , 51 ], are considered beneficial for transdisciplinary learning. However, according to the results of this study, the students of the experimental group valued these disciplines less when working individually and without being able to share resources or being able to move to creative spaces.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, unlike the first objective that we discussed, the data confirm that the pandemic, together with the preventive measures in Spanish schools, had an impact on the experimental group that developed active methodologies, as supported by the study by Ref [ 68 ], especially in PEER_INT, POST_COM and TRANS_THINK in a negative way, although above the average evaluation. That is, working in the classroom as a group or exchanging ideas among peers through fields of computational thinking, such as robotics, programing or artificial intelligence, as supported by studies by Refs [ 41 , 42 , 43 , 51 ], are considered beneficial for transdisciplinary learning. However, according to the results of this study, the students of the experimental group valued these disciplines less when working individually and without being able to share resources or being able to move to creative spaces.…”
Section: Discussionmentioning
confidence: 99%
“…In reference to the main objective of the study, “Evaluate the STEAM dimensions in sixth grade of primary education in times of pandemic”, the post-test results of the experimental group support the lines of research of Refs [ 19 , 20 ] in relation to the fact that there is little research on STEAM-EDU teaching methodologies and resources among teachers, who encountered an added difficulty during the pandemic, that is, the restrictions implemented in educational centers by the government of Spain [ 69 ]. Finally, in the experimental group, the possibility of creating, researching, interacting, exploring, developing and presenting, which are areas of the Classroom of the Future, and these actions are associated with the pyramid of Bloom’s taxonomy, are enriching cognitive processes that are achieved through computational thinking, following the lines of research in Refs [ 40 , 43 , 44 ]. In this study, the pre-test data show that they are viable but not as a result of the pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They have active thinking and like imagination and show obvious creativity and passion in many aspects (Su, Y. S et al [29]).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Scratch is a well-recognized visual programming language with a user-friendly graphical interface (Alonso, 2020). Several previous studies have reported the potential of using such visual programming systems to foster novice learners’ computational thinking (Wu & Su, 2021) and creative thinking (Su et al, 2021; Resnick et al, 2009) as well as programming syntax (Meerbaum-Salant et al, 2013).…”
Section: Introductionmentioning
confidence: 99%